Integrating Self-Determination Theory (SDT) into Islamic Education in the Digital Era: A Systematic Literature Review (2020-2026) - Azmi Himmana Ilvi; Tri Wahyudi Ramdhan; Moh Holil Baitaputra (al-Afkar, Journal For Islamic Studies, 2026)
This Systematic Literature Review (SLR) aims to explore the integration of Self-Determination Theory (SDT) within the Islamic educational ecosystem during the era of digital disruption (2020–2026). The primary focus of this research is to dissect the interaction between basic psychological needs (autonomy, competence, relatedness) and transcendental values such as Adab (ethics), Ikhlas (sincerity), and Mas’uliyyah (responsibility). Utilizing the PRISMA protocol, this study analyzes 52 reputable scientific articles to synthesize the theoretical gap between modern learner autonomy and spiritual authority in Madrasas and Pesantrens. Methodologically, the findings indicate a research transformation toward complex structural model testing (SEM) and the validation of contextual psychometric instruments. The results demonstrate that digital innovation plays a dual role: enhancing technical autonomy while simultaneously demanding a reinforcement of the teacher's role as a moral scaffold. This research successfully conceptualizes the "Spiritual Motivation" model, wherein learning is viewed as a manifestation of Fitrah (innate human nature) to seek divine blessings. It is concluded that SDT principles maintain high compatibility with Islamic pedagogy within a theocentric framework. These findings provide a theoretical contribution to Islamic educational psychology and offer practical guidance for educators in managing student motivation in the Society 5.0 era without reducing spiritual identity.